2017
DOI: 10.20360/g2gm35
|View full text |Cite
|
Sign up to set email alerts
|

The Techno-literacy Practices of Young Children from Diverse Backgrounds

Abstract: To complicate the notion of a digital divide along economic and cultural lines, this paper describes techno-literacy practices within the homes of children from diverse backgrounds. Data were drawn from two ethnographic case studies examining the home literacy practices of pre-school aged children. Participants were three Karen refugee families and two English-speaking, middle-class families. The findings suggest that children initiate interactions with digital tools within the cultural and economic landscapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Children may also access digital technology to develop language knowledge beyond English and their heritage language. For example, Friedrich et al (2017) noted how a 4-year-old Karen (Indigenous people of Myanmar) child accessed YouTube to watch cartoons in Chinese and music videos of Thai and Burmese singers performing in multiple languages.…”
Section: Inclusivity For English Language Learnersmentioning
confidence: 99%
“…Children may also access digital technology to develop language knowledge beyond English and their heritage language. For example, Friedrich et al (2017) noted how a 4-year-old Karen (Indigenous people of Myanmar) child accessed YouTube to watch cartoons in Chinese and music videos of Thai and Burmese singers performing in multiple languages.…”
Section: Inclusivity For English Language Learnersmentioning
confidence: 99%
“…For example, Flewitt and Clark (2020) found that one of the digital operational skills children learn in the home is how to engage in video calls via different social media applications. Similarly, another study showed that children learned digital operational skills using different digital technologies including tablets, smartphones, gaming consoles, laptops, DVDs, and cassette players in the home context (Friedrich et al, 2017). Plowman et al (2012) stressed that one of the significant skills children learn in the home context is digital operational skills, which play a crucial role in their everyday life to extend knowledge and understanding of the world.…”
Section: Digital Operational Skillsmentioning
confidence: 99%